Remote surgery based on 5G medical customized network practice and thoughts - Yingzhong LI (Dianxin kexue)
With the accelerated implementation of the “new infrastructure”, all sectors of society are seizing the favorable opportunity, giving full play to the institutional advantages, concentrating, accelerating the construction of 5G network, promoting the solid implementation of 5G applications, building 5G into an important engine to accelerate China's digital transformation process and boost high-quality economic development, and pressing the fast forward key for 5G wise information technology of med.Firstly, the case background of 5G remote surgery were introduced.Then, combined with the project practice, the practical results of 5G remote surgery were introduced, then combined with the application practice, the application scenario, needs and pain points, research concept, design and implementation, technology and methods of 5G remote surgery were analyzed, and a practical analysis was completed.Finally, the corresponding thinking and future prospects were given.